(untitled) (Global Journal of Management and Business Research, 2022)
Mobile payment refers to a payment method by which a consumer pays a bill for goods or services through a mobile terminal. mobile payment users can send payment instructions directly or indirectly to a bank via mobile devices, thereby enabling currency payments and funds transfers. It realizes the integration of terminal equipment, Internet, application providers and financial institutions, and completes financial business such as currency payment. However, the adoption rates of this payment method is relative low in Malaysia. This research aims to identify and explore key factors that affect the decision of whether to use mobile payments. Four wellestablished theories, Theory of Rational Action (TRA), Technology Acceptance Model (TAM), Unified Theory of Acceptance and Use of Technology (UTAUT), Compass Acceptance Model for the analysis and evaluation of mobile service (CAM) are applied to investigate user acceptance of mobile payments.